Research and nursing: a reality with plenty of successes - Cervera Vallejos, Mirtha Flor (2022)
Nursing professionals immersed in the real intrahospital, community or scientific world, developing as clinical or teaching specialists and endorsed with a specialty, master's or doctoral degree, found time available for research practice, a very typical situation in Peruvian nursing.